BEYOND THE GREEN NARRATIVE: ESG DISCLOSURE AND GREENWASHING INDICATIONS IN INDONESIAN SUSTAINABILITY REPORTS - Armadan, Avant Muhammad; Fitriaty; Muhammad Haris Saputra (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
This study examines the extent and character of Environmental, Social, and Governance (ESG) disclosure in sustainability reports issued by companies included in the IDX ESG Leaders index, and evaluates disclosure patterns that may signal greenwashing. A sequential explanatory mixed-methods design was used. The quantitative stage developed an ESG Disclosure Index by coding indicators mapped from the Global Reporting Initiative Standards with a binary score of one for disclosed items and zero for undisclosed items. The qualitative stage used document analysis supported by NVivo 12 Pro to interpret the traceability, consistency, and substantive depth of selected disclosures. The observation period covered 2022–2024. The average total disclosure index increased from 50.93% in 2022 to 56.32% in 2023 and 64.30% in 2024. Nevertheless, the growth was uneven. The qualitative findings revealed transition gaps in GRI references, inconsistent or duplicated disclosure codes, inaccessible cross-references, and exclusions justified as non-material, irrelevant, or confidential. Symbolic and substantive disclosures also appeared within the same report: some claims were supported by data, targets, mechanisms, and evaluation, while others relied mainly on commitments and positive framing. The study therefore does not label individual firms as greenwashers. Instead, it identifies disclosure conditions that warrant critical scrutiny, particularly when a strong sustainability image is not matched by balanced, traceable, and verifiable evidence. Integrating index-based measurement with qualitative interpretation provides a more cautious basis for evaluating sustainability reporting credibility.